Keefektifan Media Wordwall Terhadap Kemampuan Berhitung dan Berpikir Kritis Siswa Kelompok B TK IT Almawaddah Kota Semarang - Murgiyanti, Murgiyanti (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
There are still some children whose numeracy and critical thinking skills do not match the expected development. Learning to count and think critically still uses less varied media. Learning media can influence children's learning outcomes. The aim of this research is to determine the effectiveness of wordwall media on children's numeracy and critical thinking skills. The research was conducted at the Almawaddah IT Kindergarten, Semarang City. The research results show that wordwall media is quite effective in improving children's numeracy and critical thinking skills.